Complete mitochondrial genome of the Verticillium-wilt causing plant pathogen Verticillium nonalfalfae - Jelen, Vid; de Jonge, Ronnie; Van de Peer, Yves; Javornik, Branka; Jakše, Jernej (PLOS ONE, 2016)
Verticillium nonalfalfae is a fungal plant pathogen that causes wilt disease by colonizing the vascular tissues of host plants. The disease induced by hop isolates of V. nonalfalfae manifests in two different forms, ranging from mild symptoms to complete plant dieback, caused by mild and lethal pathotypes, respectively. Pathogenicity variations between the causal strains have been attributed to differences in genomic sequences and perhaps also to differences in their mitochondrial genomes. We used data from our recent Illumina NGS-based project of genome sequencing V. nonalfalfae to study the mitochondrial genomes of its different strains. The aim of the research was to prepare a V. nonalfalfae reference mitochondrial genome and to determine its phylogenetic placement in the fungal kingdom. The resulting 26,139 bp circular DNA molecule contains a full complement of the 14 "standard" fungal mitochondrial protein-coding genes of the electron transport chain and ATP synthase subunits, together with a small rRNA subunit, a large rRNA subunit, which contains ribosomal protein S3 encoded within a type IA-intron and 26 tRNAs. Phylogenetic analysis of this mitochondrial genome placed it in the Verticillium spp. lineage in the Glomerellales group, which is also supported by previous phylogenetic studies based on nuclear markers. The clustering with the closely related Verticillium dahliae mitochondrial genome showed a very conserved synteny and a high sequence similarity. Two distinguishing mitochondrial genome features were also found—a potential long non-coding RNA (orf414) contained only in the Verticillium spp. of the fungal kingdom, and a specific fragment length polymorphism observed only in V. dahliae and V. nubilum of all the Verticillium spp., thus showing potential as a species specific biomarker.